Pengaruh Disiplin Eksekusi (4D) terhadap Efektivitas Kerja Karyawan di Bank BJB Kantor Cabang Majalaya - Hilman S. Nurmana; Anggit Suryopratomo; Herlida Yuliani (Ma'soem University, 2022)
Based on the observations, that the background of this study is the Non PerformingLoan (NPL) target that has been experiencing fluctuations over the last three years. This study aims to find out how the influence of the four execution disciplines (focus on the very important, act on lead measure, record achievements in the scoreboard, and maintain accountability of each employee) on the effectiveness of employee work at Bank BJB Majalaya Branch Office. The object in this research is bjb bank employee of Majalaya branch office. The types of associative quantitative research, primary data types, and data collection techniques in the form of observations, interviews, library studies and questionnaires. While the sampling technique using slovin formula with a population of 60 employees obtained a sample of 38 employees. The results of the study show that there is an effect of focusing on the very important thing (X1) on employee work effectiveness (Y) by 27.7%, acting based on lead measure (X2) on employee work effectiveness (Y) by 17.8%, recording achievements in the scoreboard (X3) on the work effectiveness of employees (Y) of 42.7%, and maintaining the accountability of each employee (X4) on the effectiveness of employees' work (Y) of 35.4%. The results simultaneously X1, X2, X3, and X4 affect Y by 40.4%.